Effect of Ability on Salesperson Performance Through Adaptive Selling Behavior as an Intervening Variable - Indrawati, Sari (Universitas Dr. Soetomo, 2021)
This research was conducted at PT PX, which is a state-owned company in Indonesia appointed to produce and distribute subsidized fertilizers. PT PX is facing the risk of being diverted from fertilizer subsidies by the Government. To deal with this risk, PT PX has prepared a strategy that is to increase sales of non-subsidized fertilizers and non-fertilizer products. However, the sales performance of non-subsidized fertilizers and non-fertilizer products did not reach the target as expected. The author wants to examine whether the sales target is not achieved due to salesperson’s ability. In addition to ability, sales performance is also influenced by sales behavior done by salesperson, one of which is adaptive selling behavior. Therefore, this study was conducted to determine the ability possessed by salesperson at PT PX on sales performance through their adaptive selling behavior. This research was conducted using partial least square analysis techniques. The results of this study indicate that the salesperson's ability has a significant effect on salesperson's performance through adaptive selling behavior.